Implementation of network-based smart order system - Abd. Wahab, Mohd Helmy; Abdul Kadir, Herdawatie; Ahmad, Nadiah; Abdul Mutalib, Ariffin; Mohd Mohsin, Mohd Farhan (2008)
This paper presents the development of smart order system in restaurant.The development of the system is primarily concerned to integrate and provide network system rather than the stand alone system which indicates the use of networking capabilities could provide efficient data communication as well as improved the management in restaurant. The development of the system strictly follows the system development life cycle.Generally, the system can be divided into 2 main components which are hardware design which are not discussed in details here and system development which primarily goals of the paper.The results indicate that the system works fine with the data communication works as planned.